2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7026089
|View full text |Cite
|
Sign up to set email alerts
|

Countering anti-forensics to wavelet-based compression

Abstract: Wavelet-based compression is widely used to reduce image redundancy for efficiently storing and transmitting the data. Thus it is an important part in digital image forensics to trace the wavelet-based image compression history. The wavelet-based compression leaves comb-like quantization artifacts in the DWT (Discrete Wavelet Transform) histogram, which however can be disguised using a proper dithering operation. In this paper, standing on the forensic side, we study the joint histogram of DWT coefficients acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Anti-forensics for JPEG compression is countered by the work in [24] which uses inter-and intra-block correlations. Anti-forensics developed for wavelet-based compression techniques is countered in [25] by analyzing relations between DWT coefficients across different levels.…”
Section: Countering Anti-forensicsmentioning
confidence: 99%
“…Anti-forensics for JPEG compression is countered by the work in [24] which uses inter-and intra-block correlations. Anti-forensics developed for wavelet-based compression techniques is countered in [25] by analyzing relations between DWT coefficients across different levels.…”
Section: Countering Anti-forensicsmentioning
confidence: 99%
“…The features are then used to train a SVM classifier. The results on benchmark databases showed that this scheme is capable of detecting JPEG measures grainy noise due to anti-forensic dither in DCT domain using TV, accuracy almost 100% over QF ∈ [30,84] Wang et al [126] 2014 quantisation UCID [78](1338 greyscale 512×384 images, compression rate from 0.5 to 8bpp, SVM, JPEG2000, SPIHT)…”
Section: Aafts For Compressionmentioning
confidence: 99%
“…Wang et al [126] proposed an AAFT for wavelet-based compression. The fingerprints of counter-forensics wavelet-based compression were suppressed by analysing relationships of DWT coefficients across different decomposition levels.…”
Section: Aafts For Wavelet-based Compressionmentioning
confidence: 99%